Effect of Alkaline Activator Addition on Grout Mortar Made from Cement and Silica Fume with Si/Al Ratios - Agustin Dita Lestari; Aulia Rahman; Agus Sugiarto; Armin Naibaho (Lembaga Penelitian dan Pengabdian kepada Masyarakat ITATS, 2026)
The demand for improved material performance continues to increase as alternative materials technologies develop. Likewise with construction materials such as concrete, mortar, and the like. Grout mortar is a type of mortar that is commonly used to repair porous construction structures. As with filler materials in general, strength performance is also a demand in order to obtain a cohesive unity with the main structure. The addition of chemicals is allegedly an alternative that is worth studying to further increase the strength of materials, because changes in chemical properties will lead to changes in physical capabilities, in this context strong pressure. One example of a chemical composition that is widely used to improve the performance of a mixture is an alkaline activator due to its reactive properties. The addition of alkaline activators in certain proportions will change one of the chemical structures of the material, namely the ratio of silica and aluminum contents, or better known as the Si/Al ratio. With the benchmark in the previous study, the chemical content was analyzed by the XRF test, then a new mixture was made with a modified Si/Al ratio close to the target level, which are 4.5, 4.75, and 5. The research sample turned into a 5 x 5 x 5 cm mortar cube that was tested for compressive strength at the age of 7 and 28 days. After conducting research and analysis, it was found that none of the variations in the Si/Al ratio showed positive results in the development of compressive strength when compared to the performance of the previous sample. Only an average compressive strength of 15.8 MPa was obtained for the 7-day-old sample and 21.16 MPa at 28 days of age, while the sample was preceded at around 30 MPa and 40 MPa for the same age. This shows that the increase in the Si/Al ratio to the limit of 5 is inversely proportional to the improvement in the performance of the grout mortar.